2014
DOI: 10.1016/j.jcyt.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and limitations of natural killer cells as adoptive therapy for malignant disease

Abstract: While NK cells can be readily generated for adoptive therapy with current techniques, their optimal application to treat malignant diseases requires an appreciation of the dynamic balance between signals that either synergise with, or antagonise each other. Individuals display wide differences in NK function which determine their therapeutic efficacy. The ability of NK cells to kill target cells or produce cytokines depends on the balance between signals from activating and inhibitory cell-surface receptors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 134 publications
0
45
0
1
Order By: Relevance
“…Importantly, in both approaches, very few incidents of autoimmunity or graft-versushost reactivity were observed, arguing against missing self-attacks on normal host cells. Although some antitumor effects have been documented, the overall impression from these early trials is that there is much room for improvement (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, in both approaches, very few incidents of autoimmunity or graft-versushost reactivity were observed, arguing against missing self-attacks on normal host cells. Although some antitumor effects have been documented, the overall impression from these early trials is that there is much room for improvement (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Innate lymphoid population (NK cells, NKT cell, gdT cells) are able to respond early to inflammation and may in this way be crucial in early recognition of malignant cell alterations (Woo et al 2015). Natural killer cells have fundamental antitumoral features: They kill cells with absent or reduced MHC class I molecule expression, which is often the case during tumor progression (Davies et al 2014). Infiltration of solid tumors with NK cells may lead to a more favourable prognosis (Pietra et al 2012).…”
Section: Innate Immune Mechanismsmentioning
confidence: 99%
“…2 More recent evidence suggests that survival may be improved by haploidentical natural killer (NK) cell transplants, 3,4 and strategies that augment the efficacy of NK-cell destruction of leukemic targets would thus be of utmost clinical importance. 5 Herpes simplex virus-1 (HSV-1) is a large (.150 kb) doublestranded DNA oncolytic virus (OV) of the a-subfamily of Herpesviridae that has been engineered in various ways to preferentially infect and lyse transformed cells, leaving normal cells relatively unharmed. 6 Various OVs have shown excellent safety and promising therapeutic efficacy against solid tumors in a number of clinical trials, [7][8][9][10][11][12][13][14] and recently, Russell et al demonstrated that OV therapy may offer a therapeutic benefit for patients with hematologic malignancies.…”
Section: Introductionmentioning
confidence: 99%